PENGARUH LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN MELALUI DISIPLIN KERJA SEBAGAI VARIABEL INTERVENING PADA PDAM TIRTA KAMPAR - Herni Chania Herni Chania; Marnis Marnis; Pramadewi Arwinence (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to see the effect of the work environment and compensation onemployee performance through work discipline as an intervening variable at theregional drinking water company Tirta Kampar. The population in this study wereall employees in 2021 as many as 111 people. The number of samples in this studywas carried out by means of a saturated sampling technique (census), which madeall members of the population a sample, so that the number of samples that becamethe object of this study were 111 employees. The data analysis method used is pathanalysis using the SPSS 26 program. The results of the study found that the workenvironment and compensation had a significant effect on employee workdiscipline. Then the work environment, compensation and work discipline have asignificant effect on employee performance. Furthermore, the work environmentand compensation have a significant effect on employee performance through workdiscipline. As much as 88.1% of the research model can be explained by thevariables used in the study. Keywords: Work Environment, Compensation, Work Discipline and Performance